Socio-Economic Determinants Of Crime In Central Java: Spatial Econometrics Analysis - Muhammad Farhan Fadhillah; Diah Setyorini Gunawan; Bambang (Universitas Udayana, 2025)
Several previous studies have proven that low socio-economic factors are the causes of crime.Central Java is a province with a fairly low level of socio-economic welfare. However, thisprovince is also one of the provinces with the lowest crime rate in Indonesia. This researchaims to prove the socio-economic factors including poverty, education, unemployment, incomeper capita, and area effect on the total crime in all districts of Central Java. This research is aquantitative research using the panel data from 35 districts of Central Java in the period of2018-2022. The data was analyzed using spatial econometric methods with a panel dataapproach. Based on the results of Spatial Auto Regressive (SAR) with Fixed Effect Model(FEM) shows that education and income per capita have significant negative impact on crime.